An investigation on apportion of mathematical loss in transmission loss/cost allocation approach - Shafeeque Ahmed Kalavai; Prabhakar Karthikeyan Shanmugam (Institute of Advanced Engineering and Science, 2019)
Cost allocation of highly non-linear transmission loss is complex and essential in competitive electricity market. In most of the existing transmission loss/cost allocation approaches, real power loss depends on selection of slack bus and hence the cost of transmission losses which are allocated to the generators and the loads also varies. In this paper, a complete analysis on the impact of slack bus selection on transmission loss allocation with and without mathematical loss is made. One of the existing approaches, proportional generation and proportional load (PGPL) method is taken to illustrate the impact. Mathematical loss is the loss without generation and load in the network and can be obtained from power flow solution by taking generation and load as zero. The cost incurred for this mathematical loss is allocated to the transmission lines while the cost of transmission loss due to bilateral contracts is allocated among the sources and the consumers. These loss/cost allocations with and without considering mathematical loss is shown using an IEEE 30 bus, 57 bus, 75 bus and 118 bus systems. The simulation results are obtained using MATLAB R2014a.